Urea-N intensification and its impact on stock carbon and nitrogen content of rice fields in Aceh Utara Regency, Indonesia - Khusrizal, Khusrizal; Nasruddin, Nasruddin; Nazaruddin, Muhammad; Rusdi, Muhammad (Journal of Degraded and Mining Lands Management, 2026)
Soil Carbon Stock (SCS) plays a vital role in improving soil quality and reducing global temperatures, and nitrogen (N) is a major macronutrient plants require in large quantities. Urea-N fertilizer serves as the primary source of N and is applied in all growing seasons for irrigated and non-irrigated rice fields. The impact of intensive urea-N application on SCS and N levels in paddy soils remains a topic of discussion. This paper examined the effects of urea-N application on SCS and N content in rice fields. A total of 45 soil samples were collected from 15 soil profiles, each consisting of 3 layers (0-20, 20-40, 40-60 cm), in irrigated and non-irrigated rice fields with different growing seasons (once, twice, and thrice annually). Data indicate a pronounced concentration of SCS within surface layers (97.80-213.89 Mg C ha-1), while the CO2 content varied between 16.18-22.97 Mg ha-1. The intensive use of urea-N resulted in a significant decrease in SCS (p<0.05), but did not alter CO2 levels. The average of total N, NH4+-N, and NO3--N differed among soil layers. Nonetheless, optimal levels of these nitrogen forms are achieved with reduced fertilization, specifically by applying fertilizer twice during the two annual rice planting seasons in irrigated fields.